Social Design: Role And Role In The Management Process - Dovranova Mokhidil (Periodica Journal, 2025)
This article analyzes the theoretical foundations, methodology and practical significance of social design and management. The role of the design approach in solving pressing problems in the social sphere, the role of innovative methods and advanced experiments in the formation of effective management mechanisms are considered. Also, the viability, stability and social impact of social projects are analyzed and the stages of their implementation, monitoring and evaluation criteria are covered. The results of the study put forward theoretical and practical recommendations for the successful planning and management of projects in the social sphere.
Keywords: design; social design; research